PERANCANGAN FOOD COURT DI KOTA BANJARBARU - Anida Aulia Savitri; Indah Mutia (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Culinary is something that cannot be separated from human life. Culinary has even become a trend and is interconnected with all activities, resulting in an increase in the development of eating places in Banjarbaru City. People's lives are increasingly instantaneous and practical, influencing the increasing interest in ready-made food and drinks. Plan made Food Court in Banjarbaru City which provides various kinds of culinary delights in one place. Food court design is not only a place for eating and social interaction, but also includes supporting functions and visitor experience. By using a sense of place approach, food court can have impressions and characteristics that attract visitors to come again and again. The concept applied is biophilic architecture, it means to present food court who have space experience with the application of natural elements and nuances. Through biophilic architecture, food court can be more than just a place to eat, but create a comfortable and attractive atmosphere for visitors.